Pengaruh Determinan Indeks Kebahagiaan di Indonesia Tahun 2021 - Ariyanti Candrasari; Yuni Prihadi Utomo (Ekonomis: Journal of Economics and Business, 2026)
This study aims to observe the direction and magnitude of the influence of economic and non-economic variables on the Happiness Index in Indonesia in 2021. The analytical tool used is ordinary least squares regression analysis with cross-sectional data for 37 provinces in Indonesia in 2021 obtained from the Central Statistics Agency (CSA). The results show that the education budget variable has a negative effect on the happiness index. This phenomenon indicates an educational problem that is likely related to the use of government education funds. Meanwhile, other variables such as per capita expenditure, the Indonesian democracy index, per capita income, the open unemployment rate, and the health budget did not indicate any effect on the happiness index in Indonesia in 2021. The large number of variables that did not influence indicates that happiness in Indonesia is not supported by broad-dimensional determinants, meaning that many economic and non-economic variables are still unable to determine happiness in Indonesia.